Green Synthesis Of Silver Nanoparticles Using Curcuma Xanthorrhiza Rhizome Extract - Deva, Nathan (Universiti Sains Malaysia, 2021)
The employment of plant extract in the synthesis process of silver nanoparticles is the recent advancement in green chemistry and garnering great interest among researchers worldwide. This study mainly emphasizes on green synthesis of silver nanoparticles using Curcuma xanthorrhiza (C. xanthorrhiza) rhizome extract, which acts as a reducing and capping agent. Silver ions in the silver nitrate solution can be reduced into zero valence silver nanoparticles when the rhizome extract is mixed. The reduction of silver ions resulted in color changes in the mixture from yellow to dark brown due to the surface plasmon resonance (SPR) phenomenon. Thus, several parameters influencing the green synthesis of silver nanoparticles were optimized by manipulating variables in the experiment. Then, the synthesized silver nanoparticles were characterized via analytical equipment such as UV-Visible spectrometer and Energy Dispersive X-ray (EDX) spectrometer. The UV-Vis spectrum of the silver nanoparticles was obtained, and the maximum absorption peak was acquired at a wavelength in the range of 445 to 450 nm. Hence, the best conditions for synthesizing silver nanoparticles were determined and found to be 8 wt % rhizome extract concentration, 8 mM silver nitrate solution concentration, 1:5 rhizome extract to silver nitrate solution volume ratio, and 72 hours of incubation time. Furthermore, the EDX analysis of silver nanoparticles demonstrated a spectrum of elemental composition in which silver has the highest peak at 3 keV. Several other compounds in the spectrum indicate the presence of biomolecules from the extract on the surface of nanoparticles as a stabilizing agent. These results showed that the reduction process of silver ions using C. xanthorrhiza rhizome extract is a greener method with less toxicity and can form more refined and stable nanoparticles.